Human Resources Management Using Bee Hives to Reduce the Performance Gap : A Survey Study of the Opinion of A Sample of Asiacell Employees in Baghdad - Ali Hikmat (تنمیة الرافدین)
The research seeks to identify the impact of beehive technology on the management of human resources working within the organization under study, and its relationship to reducing the levels of the performance gap for the organization as a whole. The descriptive approach analysis was used to complete the parts of the research with its theoretical and applied aspects. The researchers also designed a questionnaire based on several ready-made indicators, after they were adapted to suit the Iraqi organization in the field of application, they were distributed to a sample of 137 individuals working within Asiacell Company in Baghdad for communications. The analysis confirmed that Asiacell Company in Baghdad wants to apply beehive technology when managing its human resources. It also works to use a set of tools to diagnose its performance gap at the financial, strategic, and marketing levels. Discussing a set of theoretical cognitive foundations for two critical variables in human resources management, specifically, and applying them to one of the successful companies in the communications field.. Providing the Iraqi library with modest scientific efforts to enhance knowledge about employing beehive technology in human resources management, after using several foreign studies in its formulation, and proposing recommendations that would address the problems related to reducing the performance gap within the Asiacell Company in Baghdad.